2007
DOI: 10.1021/ie0613467
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Phenomena during Reduction of α-NiMoO4 in Different Atmospheres:  In-Situ Thermo-Raman Spectroscopy Study

Abstract: A study by in-situ thermo-Raman spectroscopy was carried out to understand the structural changes occurring during the reduction of R-NiMoO 4 in different atmospheres (viz., H 2 , CO, and C 3 H 6 ) at different temperatures and time. In addition, the dynamics of R-NiMoO 4 during reduction/reoxidation were also investigated. The products from reoxidation of reduced R-NiMoO 4 in different atmospheres were analyzed by XRD. During the reaction of H 2 with R-NiMoO 4 at 400 °C a new band was detected at 455 cm -1 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 32 publications
(42 reference statements)
10
38
0
Order By: Relevance
“…There is also a band at around 261 cm −1 related to deformation modes of Mo-O-Mo linkage. Our results are in very good agreement with other published studies [36, 37, 40, 41]. …”
Section: Resultssupporting
confidence: 94%
“…There is also a band at around 261 cm −1 related to deformation modes of Mo-O-Mo linkage. Our results are in very good agreement with other published studies [36, 37, 40, 41]. …”
Section: Resultssupporting
confidence: 94%
“…Figure 5 illustrates that all Raman spectra have the same features. The results obtained are in agreement with the literature [28], and the small variations in the positions of the vibrational modes can be associated with the method of preparation, crystal size, morphology and strength of interaction between the ions and the degree of structural order-disorder of these materials. …”
Section: Tga Curves Of Precursor Nanorodssupporting
confidence: 90%
“…Figure . The results suggested that nanorod revealed higher amount of oxygen defects or vacancy than spherical quantum-sized and layered square microsheet (5,14). Hence, from the XPS analysis, it was confirmed that sample consists of nickel, molybdenum and oxygen element.…”
Section: Resultsmentioning
confidence: 78%
“…The strong Raman peak was observed at 818.31 cm À1 that is related to distorted MoO 6 octahedral present in sample NM-M. The Raman peak is associated with the symmetric (992.02 and 665.28 cm À1 ) and asymmetric (957.11 cm À1 ) stretching modes of the (5,6,14). The Raman peaks were slightly varied and shifted due to variation of morphology of samples.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation